PERANANAN SEKTOR PERTANIAN DALAM PEMBANGUNAN WILAYAH KABUPATEN BOYOLALI BERDASARKAN TEORI BASIS EKONOMI - Ropingi Ropingi (Sepa, 2021)
The research aims to know role of agriculture sector in information income boyolali regency, role of agriculture saw from labor multiplier in Boyolali regency. The result of the research are (1) economics sector Boyolali regency in 1997-2001 period that classified basis sector are agriculture, trade, transportation, financial, lease and company service sector;